Resisting Attempts at Organizational Socialization : Ambivalence and Resistance towards the Use of Time Registration - Borchmann, Thomas; Torpegaard, Bendt (Communication & Language at Work, 2022)
The study explores resistance towards managerial attempts at socializing workers to specific forms of behaviour. The case regards the introduction of time registration practices among upper secondary school teachers. Data originates from interviews with 31 teachers. Qualitative content analysis is used to map the stances towards time registration and their supporting arguments. The arguments supporting a negative or ambivalent stance are linked to two different norm-creating contexts and sets of rules which are viewed as the bases that legitimize resistance. Findings are that ambivalent and negative stances dominate. These stances are grounded in arguments which express both professional and political concerns. Professional concerns regard the need to protect a professional identity and the needs of clients and can be linked to norms and sets of rules acquired through professional socialization. The political concerns regard the inadequacy of time registration as a means to regulate effort. These concerns can be linked to the norms and sets of rules acquired by co-worker socialization. A critical attitude towards time registration is complicated by the fact that time registration is also championed by the union. However, both the consideration of possible negative side effects unforeseen by the union and experiences of active rule-twisting from management can make rule breaking legitimate even if the rules broken are also championed by the union.